Regulativni peskovniki za UI na zdravstvenem področju z vidika slovenske perspektive - Strnad Tomasi, Ana (Delavci in delodajalci, 2026)
The article analyses the legal and institutional framework of sandboxes at the EU level, presents the French experience and assesses the situation in Slovenia by addressing specific challenges related to digital health.
Keywords: AI; European Union; Evropska unija; France; Francija; GDPR; health data; regulativni peskovnik; regulatory sandbox; Slovenia; Slovenija; umetna inteligenca; zdravstveni podatki